Desenvolvimento de software baseado nos procedimentos DNER PRO-10 & PRO-11 para a reabilitação de pavimentos asfálticos - Prata, Bruno de Athayde (2015)
The highways, indispensable goods for the economy of the country, are means that allow the individuals to accomplish its activities, being also a link for the transport of the inputs and goods of consumption for productive chains. The highways are characterized as one of the largest public investments of the country, moreover, their maintenance and the conservation should have a main character for the roadway sector. In the several methods used in the pavements rehabilitation, the reinforcement by asphaltics layers or repavement is the process more used for this, being this intervetion type used to correct as structural as functinonal problems on pavements. The roadways organs use in its projects of rehabilitation of pavements, the normative procedures of DNER, PRO-10 and PRO-11. However, such processes are hard, because they require a high number of consultations on nomographs to obtain relative information to the parameters used in the evaluation and in the design of the reinforcement of the pavement. The main goal of this paper was develop a software to the project of pavements rehabilitation, based on the above-mentioned procedures, synthesizing them in a program of easy use to the planner, without the need of the nomographs consultation and minimizing the possibility of reading mistakes. To reach the wanted goal, the programming language used was C++, recognized as more effective in the corporate way.